2019
DOI: 10.1111/jfpp.14249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the addition of Lactobacillus casei and oligofructose on the quality parameters of orange juice and hibiscus tea mixed beverage

Abstract: The objective of this study was to evaluate the effect of the addition of Lactobacillus casei and/or oligofructose on the quality parameters of orange juice and hibiscus tea mixed beverage during refrigerated storage. The addition of the probiotic culture improved the nutritional value and the stability of the rheological parameters during storage. However, it increased the turbidity and altered the color, but with no impact on the sensory acceptance. The synbiotic product had the improved characteristics prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
(73 reference statements)
2
7
0
Order By: Relevance
“…The fermentation process can increase the shelf life of fruit and vegetable beverages, improving their nutritional and functional properties, with beneficial effects on health [16]. Recently, a wide variety of research has been focused on the production of fermented non-dairy synbiotic beverages, including different types of vegetables or fruits, such as blended carrot-orange juices and nectars with different inulin concentrations [67,68], pomegranate juices, and Cornelian cherry beverages using delignified wheat bran [69,70], clarified apple juice with oligofructose [71], orange juice with oligofructose [72], orange juices and hibiscus tea mixed beverage with oligofructose [73], and blended red fruit beverages (strawberry, blackberry and papaya) supplemented with three separate prebiotics: FOS, inulin and galactooligosaccharides [74]. Generally, the findings have indicated a good compatibility among prebiotic ingredients and vegetable beverage matrices.…”
Section: Fermented Fruit and Vegetable Beveragesmentioning
confidence: 99%
“…The fermentation process can increase the shelf life of fruit and vegetable beverages, improving their nutritional and functional properties, with beneficial effects on health [16]. Recently, a wide variety of research has been focused on the production of fermented non-dairy synbiotic beverages, including different types of vegetables or fruits, such as blended carrot-orange juices and nectars with different inulin concentrations [67,68], pomegranate juices, and Cornelian cherry beverages using delignified wheat bran [69,70], clarified apple juice with oligofructose [71], orange juice with oligofructose [72], orange juices and hibiscus tea mixed beverage with oligofructose [73], and blended red fruit beverages (strawberry, blackberry and papaya) supplemented with three separate prebiotics: FOS, inulin and galactooligosaccharides [74]. Generally, the findings have indicated a good compatibility among prebiotic ingredients and vegetable beverage matrices.…”
Section: Fermented Fruit and Vegetable Beveragesmentioning
confidence: 99%
“…Products with flow behaviour <1 are characterised as pseudoplastic. Therefore, the apparent viscosity decreases when the shear rate increases (Miranda et al ., 2019a, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…However, this probiotic culture has been mainly used in dairy products, such as fermented and non‐fermented whey beverages (Cordeiro et al ., 2019; Grom et al ., 2020), cheeses (Sperry et al ., 2018; Vasconcelos et al ., 2019), yoghurts (Velasco et al ., 2019), and ice cream (Balthazar et al ., 2018). In non‐dairy products, it was mainly used in fruit juices (Miranda et al ., 2019a, 2019b) and almond, rice berry, and sesame fermented beverages (Kemsawasd & Chaikham, 2020; Fernandes et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these beverages exhibited appropriate sensory qualities (pH, viscosity and titratable acidity) and biological activities (radical scavenging activity), with significant levels compared to unfermented drinks. Fruits and vegetables have also been focused on producing fermented non-dairy synbiotic beverages including carrot-orange juice, orange juice, hibiscus tea mixed beverages, and nectar mixed with different polysaccharide concentrations [ 115 , 116 , 117 , 118 , 119 ], and are healthy sources of antioxidants, minerals, and bioactive compounds [ 120 ]. Overall, these studies showed a strong interaction between the polysaccharides (prebiotics) and the fruit and vegetable beverage matrices.…”
Section: Functionalities and Applications Of Plant Polysaccharides In Fermented Foodsmentioning
confidence: 99%